NEGOTIATING WORK HAPPINESS UNDER EMOTIONAL DEMANDS: A PHENOMENOLOGICAL STUDY IN A SOCIAL FOUNDATION - Putu Eka Darmawan; Rosita Endang Kusmaryani; Mario Alberto Salazar-Altamirano (Psyche: Jurnal Psikologi, 2026)
Work happiness has become a central issue in organisational psychology, particularly in mission-driven settings where employees are expected to sustain commitment under emotional and resource constraints. This study explores how employees of a social foundation in Karangasem, Bali, experience and negotiate work happiness in everyday organisational life. Using a qualitative phenomenological design, the study applied Interpretative Phenomenological Analysis (IPA) to in-depth semi-structured interviews with two employees directly involved in community service. Work happiness was understood as a broad subjective experience of work as meaningful, positive, and worth sustaining, while job satisfaction, work engagement, and affective organisational commitment were treated as related but analytically distinct constructs. The findings revealed four interrelated themes: meaning of work, social relationships, emotional burden, and workplace dynamics. Participants experienced happiness through meaningful contribution, alignment between personal values and the foundation’s social mission, and supportive interpersonal relationships. However, this happiness coexisted with emotional fatigue, unclear procedures, uneven task distribution, and shifting organisational demands. The study contributes to psychological discussions on employee well-being by showing that work happiness in nonprofit settings is not the absence of strain, but a negotiated experience sustained through meaning, relational support, emotional regulation, and organisational adaptation.